The predictive value of the preoperative systemic immune‐inflammation index in the occurrence of postoperative pneumonia in non‐small cell lung cancer: A retrospective study based on 1486 cases - Jiang, Rui; Li, Pengfei; Shen, Wang; Deng, Hanyu; Qin, Changlong; Qiu, Xiaoming; Tang, Xiaojun; Zhu, Daxing; Zhou, Qinghua (Thoracic cancer, 2023)
Background To investigate the correlation between the preoperative systemic immune‐inflammation index (pSII) and postoperative pneumonia (POP) in surgical non‐small cell lung cancer patients. Methods Patients who underwent lung cancer surgery at West China Hospital of Sichuan University were retrospectively included. The indicators were collected, including basic information of patients, surgery‐related variables and POP rate. The predictive value of the pSII in the occurrence of POP was analyzed. Results A total of 1486 patients (male: 748, 50.3%; female: 738, 49.7%; mean age: 58.2 ± 9.7 years; median age: 59 years old, interquartile range: 51–65 years old) were finally included in the study, of which 142 patients had POP with an incidence of 9.5% (142/1486), 9.2% (69/748) in males, and 9.9% (73/738) in females. The proportion of patients with diabetes in the pneumonia group was significantly higher than that in the nonpneumonia group (9.8%, 14/142 vs. 5.6%, 75/1344, p = 0.041). Compared with the nonpneumonia group, the level of the preoperative body mass index (24.2 [21.9, 26.1] vs. 23.1 [21.1, 25.2], p = 0.003) and SII (487 [350, 673] vs. 345 [230, 500], p < 0.001) in the pneumonia group were significantly higher. Multiple factor analysis showed that the pSII (odds ratio: 1.001, 95% confidence interval: 1.000–1.001, p < 0.001) was an independent risk factor for POP (487 [350, 673] vs. 345 [230, 500], p < 0.001); receiver operating characteristic curve analysis showed that the pSII was effective in predicting POP (area under curve: 0.751, p < 0.001). Conclusion The pSII is closely related to and can effectively predict the occurrence of POP after lung cancer surgery. SII had better efficiency in predicting POP (AUC: 0.751, p < 0.001), and SII = 483 was the optimal cutoff point (Youden index: 0.41, sensitivity: 68.3%, specificity: 72.7%), compared to preoperative NLR and PLR which showed NLR (AUC: 0.567) and PLR (AUC: 0.582). The SII level could also effectively predict the severity of pulmonary infection (AUC: 0.793, p < 0.001).